Problematika Pemekaran Daerah: Tinjauan dari Pembentukan Undang-Undang Daerah Otonomi Baru di Papua - Rini Maisari (Universitas Islam Indonesia, 2022)
This article discusses a number of problems arising from the division of Papua into several new provinces. The background to this problem is the judicial review of laws that have been passed, the rejection from the people and the Papuan People's Council (MRP) as the cultural representation of indigenous Papuans, and the revision of the Papua Special Autonomy Law which is considered to reduce the role of the MRP and strengthen the role of the central government in carrying out expansion. The formation of the New Autonomous Region Law was considered to have taken place in a haste: the discussion was carried out for approximately 4 (four) hours and did not address the Problem Inventory List (DIM) from the DPD, thus it was considered to be implementing a Fast Track Legislation (FTL). This is a normative legal research with a statutory and conceptual approaches. The results of the study indicate that, first, the problems that arise are that the expansion was not carried out with an in-depth study and did not pay attention to the characteristics of Papua which is a conflict area. The specificity of the division of Papua which eliminates the preparatory period is predicted to cause the Papua New Guinea to become an area that fails to develop due to the unpreparedness of Papua, especially in terms of financial and economic capabilities. Second, even though the Law on New Autonomous Region was implemented quickly, it does not mean implementing an FTL since FTL is not regulated in Indonesia and the FTL that applies in other countries is only to address emergency problems where there are no clear indicators that division is an emergency matter.Keywords: Legislation Fast Track, Expansion Problems, Papua Expansion. AbstrakTulisan ini membahas sejumlah problematika yang ditimbulkan dari pemekaran Papua menjadi beberapa provinsi baru. Masalah ini dilatarbelakangi karena dilakukannya judicial review terhadap UU yang sudah disahkan, penolakan dari masyarakat dan Majelis Rakyat Papua (MRP) sebagai representasi kultulal orang asli Papua, serta revisi UU Otsus Papua yang dianggap mengurangi peran MRP dan menguatkan peran pemerintah pusat dalam melakukan pemekaran. Pembentukan UU DOB dianggap berlangsung secara cepat dan terburu-buru yakni pembahasan dilakukan kurang lebih 4 jam dan tidak membahas Daftar Inventarisasi Masalah (DIM) dari DPD, sehingga dianggap menerapkan Fast Track Legislation (FTL). Penelitian ini adalah penelitian hukum normatif dengan pendekatan peraturan perundang-undangan dan pendekatan konsep. Hasil penelitian menunjukkan bahwa, pertama, problematika yang muncul yaitu pemekaran tidak dilakukan dengan kajian secara mendalam dan tidak memperhatikan kharakteristik Papua yang merupakan daerah konflik. Kekhususan pemekaran Papua yang menghilangkan masa persiapan diprediksi menyebabkan DOB Papua menjadi daerah yang gagal berkembang karena ketidaksiapan Papua terutama dari segi kemampuan keuangan dan ekonomi. Kedua, meskipun UU DOB dilakukan secara cepat, namun bukan berarti menerapkan FTL sebab FTL tidak diatur di Indonesia dan FTL yang berlaku di negara lain hanya untuk mengatasi masalah darurat yang mana tidak ada indikator yang jelas bahwa pemekaran adalah masalah darurat.Kata-kata Kunci: Fast Track Legislation, Problematika Pemekaran, Pemekaran Papua.